Targeting Burkitt lymphoma with a tumor cell–specific heptamethine carbocyanine‐cisplatin conjugate. Issue 13 (6th March 2019) - Mrdenovic, Stefan; Zhang, Yi; Wang, Ruoxiang; Yin, Lijuan; Chu, Gina Chia‐Yi; Yin, Liyuan; Lewis, Michael; Heffer, Marija; Zhau, Haiyen E.; Chung, Leland W. K.
Abstract : Background: Burkitt lymphoma is a fast‐growing mature B cell malignancy, whose genetic hallmark is translocation and activation of the c‐myc gene. Prompt multiagent immunochemotherapy regimens can have favorable outcomes, but prognosis is poor in refractory or relapsed disease. We previously identified a novel family of near‐infrared heptamethine carbocyanine fluorescent dyes (HMCD or DZ) with tumor‐homing properties via organic anion‐transporting peptides. These membrane carriers have uptake in tumor cells but not normal cells in cell culture, mouse and dog tumor models, patient‐derived xenografts, and perfused kidney cancers in human patients. Methods: Here we report the cytotoxic effects of a synthesized conjugate of DZ with cisplatin (CIS) on B cell lymphoma CA46, Daudi, Namalwa, Raji, and Ramos cell lines in cell culture and in xenograft tumor formation. Impaired mitochondrial membrane permeability was examined as the mechanism of DZ‐CIS–induced lymphoma cell death. Results: The new conjugate, DZ‐CIS, is cytotoxic against Burkitt lymphoma cell lines and tumor models. DZ‐CIS retains tumor‐homing properties to mitochondrial and lysosomal compartments, does not accumulate in normal cells and tissues, and has no nephrotoxicity in mice. DZ‐CIS accumulated in Burkitt lymphoma cells and tumors induces apoptosis and retards tumor cell growth in culture and xenograft tumor growth in mice. Conclusion: DZ‐CIS downregulated c‐myc and overcame CIS resistance in myc ‐driven TP53‐mutated aggressive B cell Burkitt lymphoma. We propose that DZ‐CIS could be used to treat relapsed/refractory aggressive Burkitt lymphomas. Abstract : The cytotoxic effect of a synthesized conjugate between a tumor cell–specific heptamethine carbocyanine and cisplatin on Burkitt lymphoma cells is evaluated. The conjugate inhibits c‐myc expression, reduces mitochondrial membrane permeability, and induces lymphoma cell death in culture and in xenograft tumors in athymic mice.